2020
DOI: 10.1111/geb.13145
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in agroforestry systems is affected by tree species diversity, age and regional climate: A global meta‐analysis

Abstract: Aim Agroforestry is a globally practised system of land use for achieving greater and more diverse biomass production, but it has other ecological benefits, such as mitigation of climate change. Despite this, long‐term carbon (C) accumulation in different components of agroforestry systems, the drivers for C accumulation and the linkages between tree biomass and soil C stocks remain unclear. Location Global. Time period From 1989 to 2019. Major taxa studied Trees. Methods Here, we report on a global meta‐analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Since most collected studies focused on the change in SOC or STN stock in topsoil (0–30 cm) after grassland degradation, the data of soil properties such as SOC stock, STN stock, and soil BD were compiled from 0 to 30 cm soil layer. If one study reported SOC or STN stocks at different depths (e.g., 0–10 cm, 10–20 cm, and 20–30 cm), only stocks measured across the whole sampling depth were used to avoid interdependence of observations (Ma, Chen, Bork, Carlyle, & Chang, 2020). For the same purpose, only soil BD in the uppermost soil layer was collected (Jian et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since most collected studies focused on the change in SOC or STN stock in topsoil (0–30 cm) after grassland degradation, the data of soil properties such as SOC stock, STN stock, and soil BD were compiled from 0 to 30 cm soil layer. If one study reported SOC or STN stocks at different depths (e.g., 0–10 cm, 10–20 cm, and 20–30 cm), only stocks measured across the whole sampling depth were used to avoid interdependence of observations (Ma, Chen, Bork, Carlyle, & Chang, 2020). For the same purpose, only soil BD in the uppermost soil layer was collected (Jian et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In general, the effect sizes were unweighted (Shi et al, 2016), weighted by the inverse of pooled variances (Jian et al, 2016; Zhang et al, 2019) or replications (Dlamini et al, 2016; Lam et al, 2012; Ma et al, 2020; Xia et al, 2018) from previous meta‐analyses. Since not all the compiled studies presented the standard deviations of the means, and variance‐based weighting function might cause extreme weights (van Groenigen, Osenberg, & Hungate, 2011), the effect sizes were thus weighted by a function of replications in this study: W=Nnd×NdNnd+Nd, Where: W is the weight; N nd and N d are the numbers of replications at non‐degraded sites and degraded sites, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luedeling et al [30] compiled C sequestration rates of AFS located in Mozambique, Zambia and Tanzania (on sites with mean annual rainfall ranges from 500 to 1200 mm) and found values ranging from 0.22 to 5.8 Mg C ha −1 yr −1 ; rotational woodlots stored more C than other AFS in the studied regions. Ma et al [167] in a global meta-analysis of C storage within AFS reported an average of 46.1 Mg Ha −1 more C than tree-less land-use systems with systems consisting of multiple tree species storing a higher C in their collective biomass.…”
Section: Increased Potential For Carbon Sequestrationmentioning
confidence: 99%
“…In SSA, tree intercropping systems have the highest potential to sequester C (1.5 to 3.0 Mg C ha −1 yr −1 ), followed by silvopastoral systems (1.0 to 2-5 Mg C ha −1 yr −1 ) and protective systems like shelter belts (0.4 to 1.0 Mg C ha −1 yr −1 ). All estimates are highly variable, depending on agroecological distribution [2]; nevertheless, a conversion of cropland to AFS has the potential to increase SOC [167]. More research is needed in order to get consistent and reliable data [53].…”
Section: Increased Potential For Carbon Sequestrationmentioning
confidence: 99%